2001
DOI: 10.1063/1.1375829
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Origin of the deep center photoluminescence in CuGaSe2 and CuInS2 crystals [J. Appl. Phys. 86, 364 (1999)]

Abstract: In Ref. 1 the photoluminescence due to electron-hole recombination via deep donor-acceptor pairs ͑DAP's͒ in CuGaSe 2 and in CuInS 2 crystals was investigated experimentally. For the emission spectrum analysis it was stated that, for otherwise similar pairs but with the donor-acceptor separation varying-r 1 and r 2 , respectively-a difference ⌬E 12 in the emission energies would be expected

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
34
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 1 publication
5
34
1
Order By: Relevance
“…A typical PL spectrum recorded at 10 K is shown in figure 5. Photoluminescence spectra of CuInS 2 reported in earlier studies are essentially similar, although the sensitivity of our set-up is higher [46][47][48][49][50][51][52][53][54][55]. In the PL spectra, families of peaks are found which should not be regarded as experimental noise.…”
Section: Raman Spectroscopy and Photoluminescencementioning
confidence: 56%
“…A typical PL spectrum recorded at 10 K is shown in figure 5. Photoluminescence spectra of CuInS 2 reported in earlier studies are essentially similar, although the sensitivity of our set-up is higher [46][47][48][49][50][51][52][53][54][55]. In the PL spectra, families of peaks are found which should not be regarded as experimental noise.…”
Section: Raman Spectroscopy and Photoluminescencementioning
confidence: 56%
“…As is the case in other gallium chalcogenides, we believe that these pairs are due to defects in the crystal. Since the calculations on the formation energy of the defect pairs suggest that formation energy of a defect pair may be lower than the sum of two individual defects formation energies, concentration of closely spaced paired defects could easily dominate in crystals such as GaS 0.5 Se 0.5 [18]. On the other hand, the intensity of the peak energy maximum increases with increasing excitation intensity which is also characteristic of donor-acceptor pair recombination.…”
Section: Resultsmentioning
confidence: 99%
“…Photoluminescence (PL) studies on CuGaSe 2 found donor-acceptor-pair (DAP) transitions between 1.0 and 1.3 eV. 12,13 But estimations of the defect levels in these studies are based on calculations rather than measuring the activation energy directly. In Ref.…”
mentioning
confidence: 99%
“…In Ref. 12, the distance of next-nearest donor-acceptor pairs for different lattice positions was used, whereas in Ref. 13, the deep levels were calculated from the energetic position of bound excitons.…”
mentioning
confidence: 99%